Development of food-compatible encapsulation system for the protection of bioactives against environmental stressors - Goh, Joscelin Huay Yee (Nanyang Technological University, 2024)
The addition of bioactives like exogenous enzymes into animal feeds has great potential and benefits, especially in feeds that use plant-based meal as a protein source. Exogenous enzymes improve the bioavailability of protein and aid in the digestibility of the feed, thereby improving the quality of the animal feed. However, due to the sensitivity of the enzymes, there exists challenges with incorporating it into feed production as the production processes pose a high risk of degrading the enzymes due to the conditions of high temperature, moisture and pressure. As such, this work investigates the effect of heat and moisture on the enzyme activity of an enzyme, protease. Thereafter, two encapsulation systems are developed using spray drying: alginate crosslinked microparticles and alginate encapsulated chitosan-protease complex microparticles. The potential of these microparticles for applications in encapsulation for use in the fish feed manufacturing conditions consisting of stressors like heat, moisture and time was investigated. Results show that both types of encapsulation systems resulted in a higher enzyme activity as compared to pure protease under heat tests of similar temperature, moisture percentage and time. The crosslinked alginate microparticles exhibited an enzyme activity of 40.3% and 58.4%, which is better compared to pure protease which exhibit an enzyme activity of 27.8%. Similarly, when the protease was complexed with chitosan and further encapsulated in the alginate microparticles, the results observed were in the range of about 27.5-30.7 %. As such, these findings highlight the potential of spray dried systems for encapsulation of exogenous protease and subsequent incorporation into the fish feed production process.